DIFFERENCES INDICATORS IN CLINICAL EPIDEMIOLOGY AND LABORATORY FOR SUSPECT DENGUE HEMORRHAGIC FEVER IN KEBUMEN DISTRICT 2023: Perbedaan Indikator Epidemiologi Klinis dan Laboratoris Pada Dugaan Penyakit Dengue Hemorrhagic Fever di Kabupaten Kebumen 2023 - Susanto, Nugroho; Ratna Hidayani, Wuri; Subaeti, Tri (Jurnal Berkala Epidemiologi, 2025)
Background: The study in Asian and American-based surveillance data between Oct 18, 2011, and Aug 4, 2016 required 7428 patients with an estimated 2694 (36%) diagnosed laboratory-confirmed dengue, 2495 (34%) non-dengue and 2237 (30%) not inclusion criteria. The clinical signs and suspected dengue symptom address a few other diseases, thus laboratory confirmatory is best solution for diagnosis of dengue. Purpose: To determine the difference between clinical epidemiological and laboratory diagnosis of dengue hemorrhagic fever in Kebumen District. Methods: The study design was cross-sectional with 395 samples of suspected dengue disease during the 2023 period, such as DHF and DD in Kebumen District area health services. The DHF diagnostic was confirmed with positive laboratory test and studied to see differences of the clinical epidemiology and laboratory data. The data collection was carried out by reviewing medical documents from health centers and hospitals. Data were analyzed with chi square test and independent t test. Results: Clinical indicators proportion was higher for fever, 95.40% and much lower for bleeding 13.20%. The dominant contribution significant for clinical epidemiology indicator of DHF is muscle pain compared to bleeding and rash. The laboratory indicator   for platelet is low, hemoglobin normal and hematocrit   normal. The variable contributing significantly for DHF is platelet (β = 0.19) and comparison of hemoglobin (β = -0.09) and hematocrit (β = -0.06). Conclusion: Clinical indicators of DHF are higher for fever (95.40%), with muscle pain being the dominant factor. Laboratory indicators include low platelet count and normal hemoglobin and hematocrit.